Case Report: Clinical case analysis of gaucher disease management in a resource-limited setting: a single center experience from Kashigar, Xinjiang Uygur Autonomous Region, the Western China - Maimaititusvn, Gulinuer; Kulaixi, Maierhaba; Atawula, Abudouwaili; Liu, Fang (Frontiers in Pediatrics, 2025)
ObjectiveThis report presents the inaugural case of Gaucher disease identified in Kashgar Prefecture, Xinjiang, the westernmost region of China. It emphasizes an analysis of the clinical characteristics, diagnostic challenges, and treatment strategies within the unique geographical, cultural, and ethnic contexts. The study aims to investigate potential associations between environmental factors, genetic backgrounds, and lifestyle in Kashgar Prefecture, as they relate to the diagnosis, treatment, and prognosis of Gaucher disease, with the goal of optimizing diagnostic and therapeutic approaches in similar regions.MethodsWe performed a retrospective analysis of the patient's clinical data, employing advanced diagnostic methods in conjunction with multidisciplinary collaboration. The data encompassed clinical symptoms, laboratory tests, imaging examinations, genetic testing, diagnostic procedures, and individualized treatment plans.ResultsA 12-year-old female patient from Kashgar, Xinjiang, China, presented with chronic anemia, hepatosplenomegaly, thrombocytopenia, recurrentepistaxis, and osseous pain. She was diagnosed with Gaucher disease type I through genetic testing and enzymatic examination. This case represents the first reported instance of this condition in the Xinjiang region. Notably, it exhibited unique clinical features, including the age of onset, severity of symptoms, and potential regional complications. Treatment with high-dose ambroxol and imiglucerase significantly alleviated the patient's symptoms, and continuous follow-up was conducted to assess long-term efficacy.ConclusionThis report underscores the critical importance of early diagnosis and timely intervention in the management of Gaucher disease, particularly in regions with limited medical resources such as Kashgar. The successful diagnosis and treatment of this case have facilitated communication and cooperation between primary healthcare units and external medical institutions. This has further driven interactions in various aspects such as academic exchanges, teleconsultations, and medical assistance. In turn, this has provided a solid foundation for safeguarding patients’ rights and improving medical services.